2017
DOI: 10.1634/theoncologist.2016-0305
|View full text |Cite
|
Sign up to set email alerts
|

The Antiproliferative Role of Lanreotide in Controlling Growth of Neuroendocrine Tumors: A Systematic Review

Abstract: Current clinical evidence shows that lanreotide Autogel has good antiproliferative activity with favorable safety and tolerability in patients with GEP-NETs, suggesting it should be considered as an early first-line treatment in this population. Further studies are needed to assess the potential benefits of higher doses and the use of lanreotide Autogel in combination therapy and as maintenance therapy in the absence of disease progression following other therapies. 2017;22:272-285 IMPLICATIONS FOR PRACTICE: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 99 publications
(182 reference statements)
2
18
1
Order By: Relevance
“…It has been shown for example that the incidence of certain types of NETs has increased and that the survival of patients has improved over time [2]. This has been partially attributed to treatments such as somatostatin analogues [20] (time to progression prolonged by 8 months), targeted therapies such as everolimus [21] and sunitinib [22] (progression free survival benefit of about 5 months for both), and hopefully pazopanib or peptide receptor radionuclide therapy (PRRT) [23] in the future. With the latest iteration, the SEER database was enriched to include details of general metastatic sites, including lung, liver, bone and brain.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown for example that the incidence of certain types of NETs has increased and that the survival of patients has improved over time [2]. This has been partially attributed to treatments such as somatostatin analogues [20] (time to progression prolonged by 8 months), targeted therapies such as everolimus [21] and sunitinib [22] (progression free survival benefit of about 5 months for both), and hopefully pazopanib or peptide receptor radionuclide therapy (PRRT) [23] in the future. With the latest iteration, the SEER database was enriched to include details of general metastatic sites, including lung, liver, bone and brain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wide range of cell types expressing SSTs, including tumors of non-endocrine origin, and the observation that SRLs display anti-proliferative activity in preclinical models of these tumors [3,25,26,27,28], open the possibility of a wider anti-tumor use for these compounds including in patients suffering from non-endocrine neoplasia. However, no successful trials have been reported with the use of SRLs as anti-proliferative agents in non-endocrine tumors’ patients so far.…”
Section: Introductionmentioning
confidence: 99%
“…In numerous pre-clinical studies and animal studies, it was shown that SST analogs have anti-proliferative effects on NETs, as well as number of other human tumors ( 102 107 ) Two double-blind Phase 3 studies ( 108 , 109 ) in patients with advanced NETs treated with lanreotide/octreotide increased the patient's progressive free survival (PFS), which lead to FDA approval. Recent meta-analyses ( 106 , 110 ) of SST analogs anti-proliferative effects in all publications ( 106 ) or the above two studies ( 110 ), in patients with advanced NETs, demonstrate good anti-proliferative activity, significant benefit from their use resulting in disease control (HR 0.51, p < 0.01), with the response rates vs. placebo being 58 vs. 32% and a good safety profile. In general, these studies demonstrate that SST analog treatment in patients with advanced NETs result in a tumoristatic effect primarily, rather than a decrease in the tumor size.…”
Section: Sst Receptorsmentioning
confidence: 99%